Lignocellulosic nanofibrils as multifunctional component for high-performance packaging applications. (June 2022) - Zhang, Xiao; Tanguy, Nicolas R.; Chen, Heyu; Zhao, Yisu; Gnanasekar, Pitchaimari; Le Lagadec, Ronan; Yan, Ning
Abstract: Polyvinyl alcohol (PVA), a biodegradable polymer, has emerged as a promising alternative to non-biodegradable petrochemical counterparts to reduce the environmental impact of the food and medical industries. In this study, we demonstrate an environmentally friendly and low-cost strategy to broaden the application scope of PVA as a packaging material by enhancing the polymer mechanical performance and reducing its hydrophilicity. By taking advantage of hydrophobic lignin that is covalently bound to the mechanically strong cellulose nanofibrils, we demonstrated that integrating oxidized lignocellulosic nanofibrils (t-LCNF) in PVA enhanced the mechanical properties, water barrier performance, and thermal stability. With only 2 wt% t-LCNF, remarkable improvements in tensile strength (21%) and toughness (74%) were obtained compared to pristine PVA films. In addition, the integration of t-LCNF improved PVA thermal stability (+67 °C at 20 wt% t-LCNF), water barrier property (−0.67 g/(m 2 *day)*m in water vapor transmission rate at 10 wt% t-LCNF), hydrophobicity (contact angle of 97.3° at 20 wt% t-LCNF), and provided tunable UV-shielding properties. This study demonstrated the excellent promise of t-LCNF as a low-cost and multifunctional component that enhances the properties of PVA for packaging applications. Graphical Abstract: ga1